Lower Limb Progressive Resistance Training Improves Leg Strength but Not Gait Speed or Balance in Parkinson’s Disease: A Systematic Review and Meta-Analysis - Tillman, Alex; Muthalib, Makii; Hendy, Ashlee M.; Johnson, Liam G.; Rantalainen, Timo; Kidgell, Dawson J.; Enticott, Peter G.; Teo, Wei-Peng (Frontiers in Aging Neuroscience, 2015)
The use of progressive resistance training (PRT) to improve gait and balance in people with Parkinson’s disease (PD) is an emerging area of interest. However, the main effects of PRT on lower limb function such as gait, balance and leg strength in people with PD remain unclear. Therefore the aim of the meta-analysis is to evaluate the evidence surrounding the use of PRT to improve gait and balance in people with PD. Five electronic databases, from inception to December 2014, were searched to identify the relevant studies. Data extraction was performed by two independent reviewers and methodological quality assessed using the PEDro scale. Standardized mean differences (SMD) and 95% confidence intervals (CIs) of fixed and random effects models were used to calculate the effect sizes between experimental and control groups and I2 statistics were used to determine levels of heterogeneity. In total, 7 studies were identified consisting of 172 participants (Experimental n=84; Control n=88). The pooled results showed a moderate but significant effect of PRT on leg strength (SMD 1.42, 95% CI 0.464 to 2.376), however no significant effects were observed for gait speed (SMD 0.418, 95% CI -0.219 to 1.055). No significant effects were observed for balance measures included in this review. In conclusion, our results showed no discernable effect of PRT on gait and balance measures, although this is likely due to the lack of studies available. It may be suggested that PRT be performed in conjunction with balance or task-specific functional training to elicit greater lower limb functional benefits in people with PD.